The American National Red Cross Bulletin, Vol. I, No. 1, January, 1906 - American National Red Cross (Salt Lake City, UT : Project Gutenberg, 2021)
"The American National Red Cross Bulletin, Vol. I, No. 1, January, 1906" is a historical publication that documents the early activities and organizational efforts of the American National Red Cross, a charitable organization founded in the early 20th century. This bulletin was released not long after the organization was chartered by Congress and represents a significant shift in the landscape of American philanthropy during this period. The likely topic of the book centers around the establishment, goals, and membership initiatives of the American National Red Cross, illustrating its commitment to humanitarian efforts. The bulletin opens with a preface outlining the Red Cross Corporation's mission and detailing its organizational structure, including its central committee and various branch societies established across the United States and in the Philippine Islands. It discusses the need to expand the membership and emphasizes the involvement of local communities in humanitarian work. The document includes various reports such as membership applications, formal communications regarding financial audits, a summary of memberships per state, and the functioning of the organization$1 (Bs offices. Additionally, it elaborates on the financial status and operational expenditures, reinforcing the Red Cross's dedication to disaster response and humanitarian relief while appealing for greater community support and organization in the months to come. (This is an automatically generated summary.)s
Release date is 2021-09-20
hekula03, Barry Abrahamsen, and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: American National Red Cross -- Periodicals; Red Cross and Red Crescent -- Periodicals